A PHILOSOPHY ON THE OPTIMAL EXPLOITATION OF FRESH GROUND WATER IN AQUIFERS IN COASTAL AREAS - J. C. Van Dam (Lowland Technology International, 1999)
This paper deals with the exploitation of fresh groundwater in coastal areas in the context of integrated water management. Saltwater is a threat. With the recharge as an upper limit for abstraction of fresh groundwater, sustainable exploitation is possible in different ways. For sustainable exploitation of fresh ground water a certain reserve must be available to overcome periods of overdraft and little recharge. A choice must be made for the combination of a sustainable rate of abstraction and the reserve of fresh groundwater in the aquifer system. The combination to be chosen determines the layout and management of the system of abstraction and recharge works.